Role of Biochemical Parameters for The Detection of Osteopenia of Prematurity (Northern International Medical College Journal, 2024)
Background: Complications from preterm birth are the leading causes of death among children under 5 years of age, responsible for approximately 1 million deaths in 2015. Three-quarters of these deaths could be prevented with current, cost-effective interventions. Premature infants, particularly those born at